Exploring young artists’ digital performance: the impact of online community engagement and co-creation on brand love - Policarpo, P.; Guerreiro, J.; Loureiro, S. M. C.; Bilro, R. G. (2020 Global Marketing Conference at Seoul Proceedings, 2020)
New music artists have been emerging in recent years through new digital platforms and streaming services. These platforms allow artists to build a community and interact with members who share the same tastes and ideas. Hence, new artists find success through their communities’ support and engagement. The current paper explores the everexpanding connection between digital media and music – allowing fans and/or consumers to naturally build a sense of belonging to a community of a single artist and/or band (Brodie et al., 2013). Brand communities are also a place where artists and fans can develop a long-term relationship (Baldus et al., 2015) and in turn create valuable personalised experiences together (Prahalad & Ramaswamy, 2004) that will result in higher levels of engagement, or brand love (Carroll & Ahuvia, 2006; Vernuccio et al., 2015).